In-situ Growth of Platinum with Hierarchical Porosity for Low Impedance Biomedical Microelectrode Fabrication. (2016) - Ceyssens, Frederik; Sree, Sreeprasanth Pulinthanathu; Geerts, Lisa; Martens, Johan; Puers, Robert
Abstract: We report a novel process that allows depositing hierarchically porous platinum, i.e. platinum with structured pores from about 1 micron down to 3 nm in porosity, in situ on flexible microelectrodes. The process is based on molecular self-assembly of a porous silica zeotile, which is then deposited on the electrode contacts of flexible platinum electrode arrays fabricated with classic lithographic techniques. The pores are then Pt filled using atomic layer deposition (ALD) and the silica mold is removed chemically. Compared to our earlier work, the in-situ ALD step improves adhesion and allows a lower temperature budget as no sintering is required. An up to 1000x reduction in electrode impedance was measured as well as a 12x increase in charge injection capacity.